Analisis Pertanggungjawaban Pidana terhadap Kelalaian Tenaga Kesehatan yang Menyebabkan Kematian Pasien - Pratama, Aldi Yoga; Ahmad Irzal Fardiansyah; Sri Riski (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Medical negligence resulting in patient death is a critical issue in health law, as it concerns both the protection of patient rights and the responsibilities of the medical profession. This study aims to analyze the form of criminal liability imposed on healthcare providers who are negligent in carrying out their duties, leading to a patient’s death. The research employs a normative juridical method supported by an empirical approach through literature review and expert interviews. The findings indicate that gross negligence in medical practice can give rise to criminal liability even in the absence of intent, as long as there is evidence of deviation from professional standards and medical procedures. This study emphasizes the importance of applying criminal law cautiously, by prioritizing the principles of ultimum remedium and restorative justice, while also highlighting the role of ethical bodies such as the Indonesian Medical Disciplinary Board (MKDKI) in distinguishing ethical violations from criminal acts, in order to maintain a balance between patient protection and respect for the medical profession.